2021
DOI: 10.1186/s12875-021-01612-8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and attitudes towards cervical cancer screening in primary healthcare in Poland - doctors’ perspective

Abstract: Background Healthcare systems have adopted different strategies to reduce the burden of cervical cancer. In Poland, a population-based screening program was implemented in 2006, leading to a downward trend in cervical cancer burden. However, screening rates are still low in relation to other EU member states. In Poland, Pap smears are mainly performed by gynecologists rather than Primary Health Care (PHC) physicians. Little is known about the experiences and attitudes of the latter regarding ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We did not find that geolocation (urban vs rural) was associated with the willingness of the healthcare provider to perform these cancer screenings, which is similar to a previous study. 39 An explanation might be that primary healthcare institutions in Tianjin, whether in urban or rural areas, are geographically located in densely populated areas that are easily accessible. 40 Additionally, with urbanisation, several rural areas are now close to urban areas, resulting in narrowing differences between urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find that geolocation (urban vs rural) was associated with the willingness of the healthcare provider to perform these cancer screenings, which is similar to a previous study. 39 An explanation might be that primary healthcare institutions in Tianjin, whether in urban or rural areas, are geographically located in densely populated areas that are easily accessible. 40 Additionally, with urbanisation, several rural areas are now close to urban areas, resulting in narrowing differences between urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Among the survey respondents, there were 8 channels of knowledge acquisition, and only 9.9% (254/2578) had more than 4 channels of acquisition, among which the most frequent sources of acquisition were community health prevention institutions or medical institutions, followed by community-issued leaflets, then county-level hospitals and above, and the lowest were newspapers and blackboards. National and international studies have shown [ 27 , 28 ] that regular visits to physicians can awake and reinforce women’s health awareness and motivate them to learn about cervical cancer screening initiatively. In addition, the study still found that women who received lectures from professionals scored much higher than those who received them through other means, which is consistent with the Bo Song’s study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, cervical cytology (every 3 years) is funded by the public payer (free of charge) for all females aged 25–59 years [ 49 ]. Moreover, multiple educational campaigns offer free access to cervical cytology in local communities [ 50 ]. This study showed that the percentage of females who performed cytology within the last 3 years decreased with the age.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for educational campaigns on cervical cancer and screening targeting older females from rural areas and small cities without higher education. Moreover, local government, public opinion leaders, and healthcare professionals should be actively involved in screening programs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%